Heritagizing the Maestro: A Study of Dr Bhupen Hazarika Samadhi Kshetra, a Memorial Site Dedicated to Dr Bhupen Hazarika - Gogoi, Leenasri; Sarkar, Sayani (Ethnographica et Folkloristica Carpathica, 2024)
Bhupen Hazarika was a multifaceted personality known for his contributions as a singer, songwriter, composer, filmmaker, writer, and social activist from Assam, a state in the north-eastern part of India. To honour his life and works, a memorial site is constructed in the Jalukbari area of Assam. The site is called ‘Dr Bhupen Hazarika Samadhikshetra’. It is located in Guwahati city, near Gauhati University, in the state of Assam, India. The literal meaning of the Assamese words Samadhikshetra is a burial site. Through empirical research, the paper investigates the conceptual framework of heritagization as applied to Dr Hazarika’s legacy, focusing on preserving, maintaining, and celebrating his contributions to society. The study emphasises the role of the memorial site, as a tangible example of Dr Hazarika’s cultural relevance by delving further into its architectural design, symbolic elements, and commemorative features. Beyond these tangible aspects, the study also addresses the intangible values, identity and collective memories that the site evokes and preserves. The paper also explores the close interaction between the cultural and constructed heritage of the site, emphasising the need for a holistic strategy to protect and preserve the cultural past. Despite controversies and challenges over selecting the last resting place of Dr Hazarika, the Samadhikshetra stands as a tribute to his lasting influence and gratitude for his artistic legacy. Through commemorative events and ongoing public engagement, the memorial site continues to serve as a sacred space where Dr Hazarika’s spirit can live on and inspire future generations.